Electrode foil, preparation method thereof and aluminum electrolytic capacitor

By forming a porous titanium dioxide film on the surface of the aluminum foil, the problems of uneven distribution of the etching holes on the surface of the electrode foil and inconsistent length of the tunnel holes are solved, and the capacity and bending performance of the electrode foil are improved.

CN119905352AActive Publication Date: 2025-04-29DONGGUAN DONGYANG SOLAR SCI RES & DEV CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411904484.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-29
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing electrode foil and its preparation process have problems such as uneven distribution of surface etch holes and inconsistent lengths of tunnel holes, which leads to a decrease in the specific capacity of the medium and high-voltage anode foil and a decrease in capacity.

Method used

A porous titanium dioxide film was formed on the surface of the aluminum foil, and a titanium dioxide sol was prepared by the sol-gel method, and a film was applied on the surface of the aluminum foil by pulling and impregnation method. After drying, a porous titanium dioxide film was formed to achieve surface pre-distribution and improve the uniformity of the etching hole distribution and the consistency of tunnel hole length.

Benefits of technology

By forming the porous titanium dioxide film, electrode foils with uniform surface etching hole distribution and consistent tunnel hole length are obtained, which improves the capacity and bending performance of the electrode foil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905352A_ABST
    Figure CN119905352A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrode materials, and particularly relates to an electrode foil, a preparation method thereof and an aluminum electrolytic capacitor. The preparation method of the electrode foil comprises the step of forming the porous titanium dioxide film on the surface of the aluminum foil before the aluminum foil is pretreated. The preparation method is easy to operate and control, the porous titanium dioxide film is formed on the surface of the aluminum foil before pretreatment, preparation of the electrode foil with uniform surface hole forming and consistent tunnel hole length is achieved, and the electrode foil prepared through the method is high in capacity and good in bending performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode materials, and in particular relates to an electrode foil and a preparation method thereof, and an aluminum electrolytic capacitor. Background Art

[0002] Electrode foil is the core material of aluminum electrolytic capacitors, and it greatly affects the key technical indicators of aluminum electrolytic capacitors, such as capacity, leakage current, loss, life, reliability, and volume. The quality of the corrosion technology determines the specific capacitance of the electrode foil. The higher the specific capacitance, the stronger the charge storage capacity of the aluminum electrolytic capacitor. The less aluminum foil is needed to make the capacitor, and the smaller the capacitor volume. The corrosion process uses high-purity electronic aluminum foil as raw material, etches the high-purity electronic aluminum foil by chemical / electrochemical methods, and forms a large number of nano or micron-level holes on its surface and inside, thereby increasing the surface area of ​​the bare foil and achieving the purpose of increasing the specific capacitance. The uniformity of the surface etched holes and the consistency of the cross-sectional tunnel holes are crucial to the capacity of the corroded foil.

[0003] Although there is currently a public technology that uses lasers to form temperature rise points on the surface of aluminum foil to improve the uniformity of the surface of medium and high voltage anode foils, this method is costly and can easily damage the surface of the aluminum foil if not operated properly.

[0004] Therefore, the existing electrode foil and its preparation process still need to be improved. Summary of the invention

[0005] The main purpose of the present invention is to provide an electrode foil and a preparation method thereof and an aluminum electrolytic capacitor. The preparation method provided by the present invention is simple to operate and easy to control, and by forming a porous titanium dioxide film on the surface of the aluminum foil before pretreatment, the preparation of an electrode foil with uniform surface pores and consistent tunnel pore length is achieved. The electrode foil prepared by the method of the present invention has high capacity and good bending performance.

[0006] In order to achieve the above objectives, the present invention provides the following technical solutions.

[0007] A first aspect of the present invention provides a method for preparing an electrode foil, the method comprising forming a porous titanium dioxide film on the surface of the aluminum foil before pre-treating the aluminum foil.

[0008] In some embodiments of the present invention, forming the porous titanium dioxide film on the surface of the aluminum foil includes: preparing titanium dioxide sol by a sol-gel method, and coating the titanium dioxide sol on the surface of the aluminum foil by a pulling and impregnation method, and forming the porous titanium dioxide film after drying.

[0009] In some embodiments of the present invention, the pore size of the porous titanium dioxide membrane is 100 nm to 200 nm.

[0010] In some embodiments of the present invention, the titanium dioxide sol comprises a solvent and a titanium source.

[0011] In some embodiments of the invention, the solvent comprises polyethylene glycol and polyethylene.

[0012] In some embodiments of the present invention, the titanium source includes butyl titanate and titanium tetrachloride.

[0013] In some embodiments of the present invention, based on the total mass of the titanium source and the solvent, the mass percentage of the polyethylene glycol is 0.05% to 2%.

[0014] In some embodiments of the present invention, in the solvent, the mass ratio of polyethylene glycol to polyethylene is 1-3:1.5-9.

[0015] In some embodiments of the present invention, in the titanium source, the mass ratio of butyl titanate to titanium tetrachloride is 1-3:4-8.

[0016] In some embodiments of the present invention, the temperature of the titanium dioxide sol in the pulling and impregnation method is 30° C. to 60° C., and the pulling speed is 10 mm / min to 100 mm / min.

[0017] In some embodiments of the present invention, the drying temperature is 70° C. to 120° C., and the drying time is 20 min to 60 min.

[0018] In some embodiments of the present invention, the treatment solution used in the pre-treatment is a solution containing hydrochloric acid and phosphoric acid.

[0019] In some embodiments of the present invention, in the treatment solution used in the pre-treatment, the mass percentage of hydrochloric acid is 5% to 10%, and the mass percentage of phosphoric acid is 3% to 20%.

[0020] In some embodiments of the present invention, the pretreatment temperature is 30°C to 80°C.

[0021] In some embodiments of the present invention, the pretreatment time is 1 min to 20 min.

[0022] In some embodiments of the present invention, the preparation method further comprises performing primary pore formation and secondary pore expansion after the pretreatment.

[0023] In some embodiments of the present invention, the primary hole formation uses a corrosive solution containing aluminum ions.

[0024] In some embodiments of the present invention, the mass percentage of aluminum ions in the etching solution is 2% to 10%.

[0025] In some embodiments of the present invention, the etching solution is an acidic solution containing aluminum ions.

[0026] In some embodiments of the present invention, the etching solution contains hydrochloric acid and sulfuric acid.

[0027] In some embodiments of the present invention, the etching solution contains 3.0% to 10.0% by mass of hydrochloric acid and 20% to 40% by mass of sulfuric acid.

[0028] In some embodiments of the present invention, the temperature of the primary pore-forming process is 50°C to 90°C.

[0029] In some embodiments of the present invention, the time of the first-level pore generation is 10s to 60s.

[0030] In some embodiments of the present invention, the secondary pore expansion uses an electrolyte containing aluminum ions.

[0031] In some embodiments of the present invention, the mass percentage of aluminum ions in the electrolyte is 0.5% to 4.5%.

[0032] In some embodiments of the present invention, the electrolyte is an acidic solution containing aluminum ions.

[0033] In some embodiments of the present invention, the electrolyte contains nitric acid and phosphoric acid.

[0034] In some embodiments of the present invention, the electrolyte contains 2.5% to 7.5% by mass of nitric acid and 0.02% to 0.25% by mass of phosphoric acid.

[0035] In some embodiments of the present invention, the temperature of the secondary hole expansion is 60°C to 95°C.

[0036] In some embodiments of the present invention, the current density of the secondary pore expansion is 0.1A / cm 2 ~3A / cm 2 .

[0037] In some embodiments of the present invention, the effective power-on time for the secondary hole expansion is 6 minutes to 30 minutes.

[0038] In some embodiments of the present invention, the preparation method further comprises post-processing.

[0039] In some embodiments of the present invention, the post-treatment uses a solution containing nitric acid.

[0040] In some embodiments of the present invention, the mass percentage of nitric acid in the solution containing nitric acid is 3% to 10%.

[0041] In some embodiments of the present invention, the post-treatment temperature is 60°C to 80°C.

[0042] In some embodiments of the present invention, the post-treatment time is 1 min to 10 min.

[0043] In some embodiments of the present invention, the preparation method further comprises removing the porous titanium dioxide film before performing the post-treatment.

[0044] In some embodiments of the present invention, the porous titanium dioxide film is removed by a drying method.

[0045] In some embodiments of the present invention, the drying temperature is 50°C to 100°C.

[0046] In some embodiments of the present invention, the drying time is 20 min to 60 min.

[0047] A second aspect of the present invention provides an electrode foil, which is prepared by the preparation method described in the first aspect.

[0048] A third aspect of the present invention provides an aluminum electrolytic capacitor, which includes an electrode foil prepared by the preparation method described in the first aspect or the electrode foil described in the second aspect.

[0049] Compared with the prior art, the present invention achieves the following technical effects:

[0050] 1) In the preparation method of the present invention, a porous titanium dioxide film is first formed on the surface of the aluminum foil, and pre-holes are arranged, and the pores are orderly distributed on the surface of the aluminum foil, thereby obtaining an electrode foil with uniform surface etched holes, achieving uniform surface pores and consistent tunnel hole lengths, and improving the capacity of the electrode foil.

[0051] 2) In the preparation method of the present invention, the thinning degree of the electrode foil surface is reduced by forming a porous titanium dioxide film.

[0052] 3) In the preparation method of the present invention, the controllable porous titanium dioxide film is formed to reduce the surface capacity loss of the electrode foil and improve the capacity of the electrode foil.

[0053] 4) In the preparation method of the present invention, under the condition of constant amount of added electricity, the pore size of the titanium dioxide film can be controlled by adjusting the amount of solvent added in the sol-gel method, thereby achieving the purpose of consistent pore depth and effectively improving the bending performance of the corrosion foil.

[0054] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only used for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. In the accompanying drawings:

[0056] Figure 1 is a surface morphology image of the electrode foil prepared in Example 1 of the present invention;

[0057] Figure 2 is a cross-sectional morphology diagram of the electrode foil prepared in Example 1 of the present invention;

[0058] Figure 3 This is a surface morphology image of the electrode foil prepared in Comparative Example 1 of the present invention;

[0059] Figure 4 This is a cross-sectional morphology diagram of the electrode foil prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0060] The exemplary embodiments of the present invention will be described in more detail below with reference to specific embodiments. It should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0061] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0062] In the description of the embodiments of the present invention, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.

[0063] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0064] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this document generally indicates that the associated objects before and after are in an "or" relationship.

[0065] The existing conventional preparation processes mostly use pre-treatment, primary pore formation, secondary electrochemical pore expansion process and post-treatment, which have the disadvantages of uneven distribution of surface pores, poor pore formation uniformity, enlarged corrosion holes after secondary electrochemical pore expansion, resulting in surface pore merging, and severe thinning of the corrosion foil surface, resulting in a decrease in the specific volume of the medium and high voltage anode foil, which greatly reduces the capacity of the medium and high voltage anode foil.

[0066] In order to improve the uniformity of the distribution of etched holes on the surface of medium and high voltage anode foil and the consistency of the length of the tunnel holes, it is reported in the literature that laser temperature rise points can be formed on the aluminum foil by laser, and the number of laser temperature rise points is set to multiple. The number of lasers is set to 2, symmetrically arranged on both sides of the aluminum foil, and the temperature of the generated focus point is lower than 600°C. The above method can obtain a corrosion foil with uniform distribution of etched holes on the surface, but more equipment is used, the process is more complicated, the cost is higher, and the local temperature of the aluminum foil exceeds 300°C, which may cause recrystallization.

[0067] Therefore, providing a simple and reliable method to obtain an electrode foil with uniform surface etch pit distribution and consistent tunnel hole length, such as a medium and high voltage anode foil, plays an important role in reducing production costs and improving product performance.

[0068] The invention provides a method for preparing an electrode foil. The method comprises forming a porous titanium dioxide film on the surface of the aluminum foil before pre-treating the aluminum foil.

[0069] In an embodiment of the present invention, a porous titanium dioxide film is first formed on the surface of the aluminum foil before pre-treatment, and the holes are pre-distributed, and the holes are orderly distributed on the surface of the aluminum foil, thereby obtaining an electrode foil with uniform surface etch holes, thereby improving the capacity of the electrode foil.

[0070] Pre-layout holes

[0071] In an embodiment of the present invention, holes are first pre-arranged on the surface of the aluminum foil, specifically, a porous titanium dioxide film is formed on the surface of the aluminum foil. It can be understood that a layer of porous titanium dioxide film is first formed on the surface of the aluminum foil to pre-arrange holes on the surface of the aluminum foil, thereby obtaining an electrode foil with uniform distribution of surface etched holes.

[0072] In the embodiment of the present invention, the titanium dioxide sol is prepared by the sol-gel method, and the titanium dioxide sol is coated on the surface of the aluminum foil by the pulling and dipping method, and a porous titanium dioxide film is formed on the surface of the aluminum foil after drying.

[0073] In an embodiment of the present invention, the pore size of the porous titanium dioxide film is in the range of 100nm to 200nm. The pore size of the porous titanium dioxide film provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 100nm to 150nm, or 150nm to 200nm, and so on. Exemplarily, the pore size of the porous titanium dioxide film can be one of 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm or any value that satisfies the above range value.

[0074] Sol-gel method

[0075] In an embodiment of the present invention, the titanium dioxide sol comprises a solvent and a titanium source.

[0076] In an embodiment of the present invention, the titanium source includes butyl titanate and titanium tetrachloride.

[0077] In some embodiments of the present invention, in the titanium source, the mass ratio of butyl titanate to titanium tetrachloride is 1 to 3:4 to 8. The mass ratio of butyl titanate to titanium tetrachloride provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, for example, it can be 1:4 to 8, it can be 3:4 to 8, it can also be 1 to 3:4, it can also be 1 to 3:8, and so on. Exemplarily, the mass ratio of butyl titanate to titanium tetrachloride can be one of 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 2:5, 2:7, 3:4, 3:5, 3:6, 3:7, 3:8 or any value that satisfies the above range value.

[0078] In an embodiment of the present invention, the solvent includes polyethylene glycol and polyethylene.

[0079] In some embodiments of the present invention, in the solvent, the mass ratio of polyethylene glycol to polyethylene is 1 to 3: 1.5 to 9. The mass ratio of polyethylene glycol to polyethylene provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, for example, it can be 1 to 3: 1.5, it can be 1 to 3: 9, it can also be 1: 1.5 to 9, it can also be 3: 1.5 to 9, and so on. Exemplarily, the mass ratio of polyethylene glycol to polyethylene can be 1: 0.5, 1: 1, 1: 1.5, 1: 2, 1: 3, 1: 4, 1: 5, 1: 6, 1: 7, 1: 8, 1: 9, 2: 1.5, 2: 3, 2: 5, 2: 7, 2: 9, 3: 2, 3: 4, 3: 5, 3: 7, 3: 8 or any value that satisfies the above range value.

[0080] In some embodiments of the present invention, based on the total mass of the titanium source and the solvent, the mass percentage of polyethylene glycol is 0.05% to 2%. The mass percentage of polyethylene glycol provided by the present invention can be the value of the interval composed of any two values ​​in the above interval, such as 0.05% to 1%, or 1% to 2%, and so on. The mass percentage of polyethylene glycol provided by the present invention can also be 0.05%, 0.06%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2% or any value that meets the above range value.

[0081] It is worth mentioning that the process of preparing titanium dioxide sol by sol-gel method in the embodiment of the present invention includes hydrolysis, polycondensation and drying and aging. The titanium source is first dispersed in a solvent containing polyethylene glycol and polyethylene, and then the active monomer is generated by hydrolysis reaction, and the active monomer is polymerized to form a sol. After a period of drying and aging, the desired titanium dioxide sol is obtained. The drying and aging temperature in the sol-gel method is 50°C to 100°C, and the drying and aging time is 1 to 4 days. Exemplarily, the drying and aging temperature of the sol-gel method can be one of 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or any value that satisfies the above range value. The drying and aging time can be one of 1 day, 1.5 days, 2 days, 2.5 days, 3 days, 3.5 days, 4 days or any value that satisfies the above range value.

[0082] Pulling and impregnation method

[0083] In the embodiment of the present invention, the pulling and dipping method is a method of vertically dipping the aluminum foil into the titanium dioxide sol, then vertically pulling the aluminum foil up from the titanium dioxide sol at a low speed, and making the attached liquid film gel in the air.

[0084] In some embodiments of the present invention, the Czochralski method may also be understood as the dipping Czochralski method.

[0085] In some embodiments of the present invention, the pulling speed is 10mm / min to 100mm / min. The pulling speed provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, for example, it can be 10mm / min to 40mm / min, or 40mm / min to 70mm / min, or 70mm / min to 100mm / min, and so on. Exemplarily, the pulling speed in the present invention can be one of 10mm / min, 20mm / min, 30mm / min, 40mm / min, 50mm / min, 60mm / min, 70mm / min, 80mm / min, 90mm / min, 100mm / min or any value that satisfies the above range.

[0086] In some embodiments of the present invention, the temperature of the titanium dioxide sol in the pulling and impregnation method is 30°C to 60°C. The temperature of the titanium dioxide sol in the pulling and impregnation method provided by the present invention can be a value in the interval composed of any two values ​​in the above range, for example, it can be 30°C to 45°C, or it can be 45°C to 60°C, and so on. Exemplarily, the temperature of the titanium dioxide sol in the present invention can be one of 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C or any value that satisfies the above range.

[0087] In an embodiment of the present invention, the temperature for drying the titanium dioxide sol after coating the aluminum foil surface by the pull-up dipping method is 70°C to 120°C, and the drying time is 20min to 60min. The temperature for drying the titanium dioxide sol after coating the aluminum foil surface by the pull-up dipping method of the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 70°C to 90°C, or 90°C to 120°C, and so on. Exemplarily, the drying temperature provided by the present invention can be one of 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, or any numerical value that satisfies the above range value. The time for drying the titanium dioxide sol after coating the aluminum foil surface by the pull-up dipping method of the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 20min to 40min, or 40min to 60min, and so on. The drying time provided by the present invention can be one of 20 min, 30 min, 40 min, 50 min, 60 min or any value within the above range.

[0088] In an embodiment of the present invention, a titanium dioxide sol is prepared by a sol-gel method, the titanium source includes butyl titanate and titanium tetrachloride, a solvent containing polyethylene glycol and polyethylene is used, and the mass percentage of polyethylene glycol is 0.05% to 2% based on the total mass of the titanium source and the solvent; and the titanium dioxide sol is coated on the surface of an aluminum foil by a pulling and impregnation method, and a porous titanium dioxide film is formed on the surface of the aluminum foil after drying, the temperature of the titanium dioxide sol is 30°C to 60°C, the pulling speed is 10mm / min to 100mm / min, the drying temperature is 70°C to 120°C, and the drying time is 20min to 60min.

[0089] Pre-treatment

[0090] In an embodiment of the present invention, the aluminum foil after the pre-hole arrangement is pre-treated to remove grease and oxide film on the surface of the aluminum foil and increase active points on the surface of the aluminum foil.

[0091] In an embodiment of the present invention, the treatment solution used in the pre-treatment is a solution containing hydrochloric acid (HCl) and phosphoric acid (H3PO4).

[0092] In some embodiments of the present invention, in the treatment solution used in the pretreatment, the mass percentage of hydrochloric acid is 5% to 10%, and the mass percentage of phosphoric acid is 3% to 20%. Exemplarily, the mass percentage of hydrochloric acid in the treatment solution used in the pretreatment provided by the present invention can be 5%, 6%, 7%, 8%, 9%, 10% or any value that meets the above range value. The mass percentage of phosphoric acid in the treatment solution used in the pretreatment provided by the present invention can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or any value that meets the above range value.

[0093] In some embodiments of the present invention, the temperature of the pretreatment is 30° C. to 80° C., which can be understood as the temperature of the treatment liquid used in the pretreatment is 30° C. to 80° C. Exemplarily, the temperature of the pretreatment can be one of 30° C., 35° C., 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C. or any value satisfying the above range.

[0094] In some embodiments of the present invention, the time of pretreatment is 1min to 20min. The time of pretreatment provided by the present invention can be the value of the interval composed of any two values ​​in the above interval, such as 1min to 6min, 6min to 12min, 12min to 20min, and so on. Exemplarily, the time of pretreatment can be 1min, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min, 14min, 15min, 16min, 17min, 18min, 19min, 20min or any value that satisfies the above range value.

[0095] In an embodiment of the present invention, the aluminum foil with a porous titanium dioxide film formed on its surface is pretreated in a treatment solution containing hydrochloric acid and phosphoric acid. The pretreatment temperature is 30° C. to 80° C. and the time is 1 min to 20 min.

[0096] First level hole

[0097] In an embodiment of the present invention, the pre-treated aluminum foil is subjected to primary pore formation.

[0098] In the embodiment of the present invention, the primary pores are formed by using aluminum ions (Al 3+ ) of corrosive liquid.

[0099] In some embodiments of the present invention, the mass percentage of aluminum ions in the etching solution is 2% to 10%. For example, the mass percentage of aluminum ions in the etching solution can be one of 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any value that satisfies the above range.

[0100] In some embodiments of the present invention, the etching solution contains aluminum ions (Al 3+ ) of an acidic solution.

[0101] In some embodiments of the present invention, the etching solution contains hydrochloric acid (HCl) and sulfuric acid (H2SO4).

[0102] In some embodiments of the present invention, the etching solution contains 3.0% to 10.0% hydrochloric acid and 20% to 40% sulfuric acid by mass. Exemplarily, the mass percentage of hydrochloric acid in the etching solution provided by the present invention can be one of 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0% or any value that satisfies the above range. The mass percentage of sulfuric acid in the etching solution provided by the present invention can be a value in the interval composed of any two values ​​in the above interval, such as 20% to 30%, or 30% to 40%, and so on. The mass percentage of sulfuric acid in the etching solution provided by the present invention can also be one of 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40% or any value satisfying the above range.

[0103] In some embodiments of the present invention, the temperature of the primary pore is 50°C to 90°C. It can be understood that the temperature of the etching solution used in the primary pore can be a value in the interval composed of any two values ​​in the above range, such as 50°C to 60°C, 60°C to 80°C, 80°C to 90°C, and so on. Exemplarily, the temperature of the primary pore can be one of 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, or any value that satisfies the above range.

[0104] In some embodiments of the present invention, the time of the first-level pore is 10s to 60s. The time of the first-level pore provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, for example, it can be 10s to 30s, or 30s to 60s, and so on. Exemplarily, the time of the first-level pore can be one of 10s, 15s, 20s, 25s, 30s, 40s, 50s, 60s or any value that satisfies the above range.

[0105] In an embodiment of the present invention, the first-level pore formation uses a corrosive solution containing aluminum ions, hydrochloric acid and sulfuric acid, and the temperature of the first-level pore formation is 50° C. to 90° C., and the time is 10s to 60s.

[0106] Secondary expansion

[0107] In an embodiment of the present invention, the aluminum foil after the primary hole expansion is subjected to secondary hole expansion.

[0108] In an embodiment of the present invention, the secondary pore expansion uses an electrolyte containing aluminum ions.

[0109] In an embodiment of the present invention, the mass percentage of aluminum ions in the electrolyte is 0.5% to 4.5%. The mass percentage of aluminum ions in the electrolyte provided by the present invention can be a value in the interval formed by any two values ​​in the above range, such as 0.5% to 3.0%, or 3.0% to 4.5%, and so on. Exemplarily, the mass percentage of aluminum ions in the electrolyte can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5% or any value that meets the above range.

[0110] In some embodiments of the present invention, the electrolyte contains aluminum ions (Al 3+ ) of an acidic solution.

[0111] In some embodiments of the present invention, the electrolyte contains nitric acid (HNO3) and phosphoric acid (H3PO4).

[0112] In some embodiments of the present invention, the electrolyte contains 2.5% to 7.5% by mass of nitric acid and 0.02% to 0.25% by mass of phosphoric acid. Exemplarily, the mass percentage of nitric acid in the electrolyte provided by the present invention can be a value in the interval composed of any two values ​​in the above interval, such as 2.5% to 4.5%, or 4.5% to 7.5%, and so on. The mass percentage of nitric acid in the electrolyte provided by the present invention can be 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6.0%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7.0%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5% or any value satisfying the above range. The mass percentage of phosphoric acid in the electrolyte provided by the present invention can be the value of the interval composed of any two values ​​in the above interval, such as 0.02% to 0.1%, or 0.1% to 0.25%, and so on. The mass percentage of nitric acid in the electrolyte provided by the present invention can be one of 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25% or any value satisfying the above range.

[0113] In some embodiments of the present invention, the temperature of the secondary hole expansion is 60°C to 95°C. The temperature of the secondary hole expansion provided by the present invention can be a value of an interval consisting of any two values ​​in the above range, for example, it can be 60°C to 75°C, or 75°C to 95°C, and so on. It can be understood that the temperature of the electrolyte used for the secondary hole expansion is one of 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, or any value that meets the above range.

[0114] In some embodiments of the present invention, the current density of the secondary hole expansion is 0.1A / cm 2 ~3A / cm 2 For example, the current density of the secondary hole expansion can be 0.1A / cm 2 , 0.2A / cm 2 , 0.5A / cm 2 , 0.8A / cm2 , 1.0A / cm 2 , 1.2A / cm 2 , 1.4A / cm 2 , 1.5A / cm 2 , 1.6A / cm 2 , 1.8A / cm 2 , 2.0A / cm 2 , 2.2A / cm 2 , 2.4A / cm 2 , 2.5A / cm 2 , 2.6A / cm 2 , 2.8A / cm 2 、3A / cm 2 or any value that satisfies the above range.

[0115] In some embodiments of the present invention, the effective power-on time of the secondary hole expansion is 6min to 30min. The effective power-on time of the secondary hole expansion provided by the present invention can be the value of the interval composed of any two values ​​in the above interval, for example, it can be 6min to 15min, or it can be 15min to 30min, and so on. Exemplarily, the effective power-on time of the secondary hole expansion can be 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min, 14min, 15min, 16min, 17min, 18min, 19min, 20min, 21min, 22min, 23min, 24min, 25min, 26min, 27min, 28min, 29min, 30min or any value that satisfies the above range value.

[0116] In the embodiment of the present invention, the secondary pore expansion adopts an electrolyte containing aluminum ions, nitric acid and phosphoric acid, the temperature of the secondary pore expansion is 60°C to 95°C, and the current density is 0.1A / cm 2 ~3A / cm 2 The effective power-on time is 6min to 30min.

[0117] It is worth mentioning that in the embodiment of the present invention, before removing the porous titanium dioxide film, the aluminum foil after the secondary pore expansion treatment can be washed with water as needed to remove the acid remaining on the surface of the aluminum foil, for example, by washing the surface of the aluminum foil with pure water.

[0118] Membrane Removal

[0119] In an embodiment of the present invention, the porous titanium dioxide film on the surface of the aluminum foil after the secondary pore expansion is removed by drying.

[0120] In some embodiments of the present invention, the drying temperature for film removal is 50° C. to 100° C. For example, the drying temperature for film removal can be one of 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C., 95° C., 100° C. or any value satisfying the above range.

[0121] In some embodiments of the present invention, the drying time for film removal is 20 min to 60 min. Exemplarily, the drying time for film removal can be one of 20 min, 30 min, 40 min, 50 min, 60 min or any value satisfying the above range.

[0122] In an embodiment of the present invention, the porous titanium dioxide film on the surface of the aluminum foil after the secondary pore expansion is removed by a drying method, the drying temperature is 50° C. to 100° C., and the drying time is 20 min to 60 min.

[0123] Post-processing

[0124] In an embodiment of the present invention, the aluminum foil after the porous titanium dioxide film is removed is post-treated to remove the aluminum ions remaining on the surface of the aluminum foil through a replacement reaction.

[0125] In an embodiment of the present invention, the post-treatment uses a solution containing nitric acid.

[0126] In some embodiments of the present invention, the mass percentage of nitric acid in the solution containing nitric acid is 3% to 10%. Exemplarily, the mass percentage of nitric acid in the solution containing nitric acid can be one of 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any value satisfying the above range.

[0127] In some embodiments of the present invention, the post-treatment temperature is 60° C. to 80° C., which can be understood as the temperature of the solution containing nitric acid used in the post-treatment is 60° C. to 80° C. Exemplarily, the post-treatment temperature can be one of 60° C., 65° C., 70° C., 75° C., 80° C. or any value satisfying the above range.

[0128] In some embodiments of the present invention, the post-treatment time is 1 min to 10 min. Exemplarily, the post-treatment time can be one of 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min or any value satisfying the above range.

[0129] In some embodiments of the present invention, the post-treatment uses a solution containing nitric acid, the post-treatment temperature is 60° C. to 80° C., and the post-treatment time is 1 min to 10 min.

[0130] In an embodiment of the present invention, the method for preparing the electrode foil includes forming a porous titanium dioxide film on the surface of the aluminum foil before pretreatment, and sequentially performing primary pore formation, secondary pore expansion, film removal and posttreatment after the pretreatment.

[0131] The present invention also provides an electrode foil, which is prepared by the above-mentioned preparation method.

[0132] In an embodiment of the present invention, the electrode foil may be a medium-high voltage anode foil.

[0133] The present invention also provides an aluminum electrolytic capacitor, which includes the electrode foil prepared by the above preparation method or the above electrode foil.

[0134] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The experimental reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the amounts of the experimental reagents, unless otherwise specified, are the amounts of reagents used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0135] Example 1

[0136] A method for preparing an electrode foil comprises the following steps:

[0137] Pre-hole arrangement: Butyl titanate and titanium tetrachloride with a mass ratio of 2:5 are used as titanium sources, polyethylene glycol and polyethylene with a mass ratio of 2:6 are used as solvents, and based on the total mass of the titanium source and the solvent, the mass percentage of polyethylene glycol is 0.05%, and titanium dioxide sol is prepared by a sol-gel method, and the titanium dioxide sol is coated on the surface of aluminum foil by a pulling and impregnation method. The temperature of the titanium dioxide sol is 50°C, the pulling speed is 80 mm / min, and after drying at 100°C for 40 minutes, a porous titanium dioxide film with a pore size of 100nm to 200nm is formed on the surface of the aluminum foil to achieve pre-hole arrangement on the surface of the aluminum foil.

[0138] Pretreatment: The aluminum foil with titanium dioxide film formed on the surface was placed in a pretreatment solution containing hydrochloric acid and phosphoric acid at 70° C. for 3 minutes, wherein the mass percentage of hydrochloric acid in the pretreatment solution was 6.0% and the mass percentage of phosphoric acid was 8.0%.

[0139] First-stage pore formation: The pre-treated aluminum foil is placed in a 72°C etching solution for 20 seconds; the etching solution is an aqueous solution containing hydrochloric acid, sulfuric acid and aluminum ions, with the mass percentage of hydrochloric acid being 5.2%, the mass percentage of sulfuric acid being 25%, and the mass percentage of aluminum ions being 5.5%.

[0140] Secondary hole expansion: The aluminum foil after primary hole expansion is placed in an electrolyte at 73°C for hole expansion. The electrolyte is a mixture of nitric acid, aluminum ions and phosphoric acid. The mass percentage of nitric acid is 5.0%, the mass percentage of aluminum ions is 3.5%, and the mass percentage of phosphoric acid is 0.08%. The current density of the secondary hole expansion is 0.2A / cm 2 , the total effective power-on time is 9 minutes.

[0141] Water washing and film removal: The aluminum foil after secondary pore expansion is rinsed with pure water, and then the porous titanium dioxide film on the surface of the aluminum foil is removed by drying. The drying temperature is 70°C and the drying time is 30 minutes.

[0142] Post-treatment: The aluminum foil after the porous titanium dioxide film is removed is placed in a 4.0% by mass nitric acid aqueous solution at 65° C. for 2 minutes.

[0143] Example 2

[0144] A method for preparing an electrode foil comprises the following steps:

[0145] The remaining operations were the same as those in Example 1, except that the mass percentage of polyethylene glycol was 1%.

[0146] Example 3

[0147] A method for preparing an electrode foil comprises the following steps:

[0148] The remaining operations were the same as those in Example 1, except that the mass percentage of polyethylene glycol was 2%.

[0149] Example 4

[0150] A method for preparing an electrode foil comprises the following steps:

[0151] The remaining operations were the same as those in Example 1, except that the temperature of the titanium dioxide sol in the immersion pulling method was 30°C.

[0152] Example 5

[0153] A method for preparing an electrode foil comprises the following steps:

[0154] The remaining operations are the same as those in Example 1, except that the temperature of the titanium dioxide sol in the immersion pulling method is 45°C.

[0155] Example 6

[0156] A method for preparing an electrode foil comprises the following steps:

[0157] The remaining operations are the same as those in Example 1, except that the temperature of the titanium dioxide sol in the immersion pulling method is 60°C.

[0158] Example 7

[0159] A method for preparing an electrode foil comprises the following steps:

[0160] The remaining operations are the same as those in Example 1, except that the pulling speed in the immersion pulling method is 10 mm / min.

[0161] Example 8

[0162] A method for preparing an electrode foil comprises the following steps:

[0163] The remaining operations are the same as those in Example 1, except that the pulling speed in the immersion pulling method is 50 mm / min.

[0164] Example 9

[0165] A method for preparing an electrode foil comprises the following steps:

[0166] The remaining operations are the same as in Example 1, except that the pulling speed in the immersion pulling method is 100 mm / min.

[0167] Comparative Example 1

[0168] A method for preparing an electrode foil comprises the following steps:

[0169] Pretreatment: The aluminum foil was placed in a pretreatment solution containing hydrochloric acid and phosphoric acid at 70° C. for 3 min, wherein the mass percentage of hydrochloric acid in the pretreatment solution was 6.0% and the mass percentage of phosphoric acid was 8.0%.

[0170] First-stage pore formation: The pre-treated aluminum foil is placed in a 72°C etching solution for 20 seconds; the etching solution is an aqueous solution containing hydrochloric acid, sulfuric acid and aluminum ions, with the mass percentage of hydrochloric acid being 5.2%, the mass percentage of sulfuric acid being 25%, and the mass percentage of aluminum ions being 5.5%.

[0171] Secondary hole expansion: The aluminum foil after primary hole expansion is placed in an electrolyte at 73°C for hole expansion. The electrolyte is a mixture of nitric acid, aluminum ions and phosphoric acid. The mass percentage of nitric acid is 5.0%, the mass percentage of aluminum ions is 3.5%, and the mass percentage of phosphoric acid is 0.08%. The current density of the secondary hole expansion is 0.2A / cm 2 , the total effective power-on time is 9 minutes.

[0172] Water washing: Rinse the aluminum foil after secondary hole expansion with pure water.

[0173] Post-treatment: The washed aluminum foil was placed in a 4.0% by mass nitric acid aqueous solution at 65°C for 2 minutes.

[0174] Comparative Example 2

[0175] A method for preparing an electrode foil comprises the following steps:

[0176] The remaining operations were the same as those in Example 1, except that the mass percentage of polyethylene glycol added was 0.02%.

[0177] Comparative Example 3

[0178] A method for preparing an electrode foil comprises the following steps:

[0179] The remaining operations were the same as those in Example 1, except that the mass percentage of polyethylene glycol added was 3%.

[0180] Comparative Example 4

[0181] The remaining operations were the same as in Example 1, except that the mass ratio of polyethylene glycol to polyethylene was 1:10.

[0182] Comparative Example 5

[0183] The remaining operations are the same as those in Example 1, except that the mass ratio of butyl titanate to titanium tetrachloride is 1:9.

[0184] Performance Testing

[0185] (1) Morphology detection.

[0186] The samples prepared in the embodiments and comparative examples were subjected to resin sample preparation and polishing, and then observed under an electron microscope.

[0187] Figure 1 This is the surface morphology of the etched holes of the electrode foil obtained in Example 1, from which it can be seen that the etched holes on the surface of the electrode foil are evenly distributed and there are relatively few holes. Figure 2 This is the cross-sectional morphology of the etched hole of the electrode foil obtained in Example 1, from which it can be seen that the tunnel hole length is consistent.

[0188] Figure 3 This is the surface morphology of the etched holes of the electrode foil obtained in Comparative Example 1. It can be seen that the surface uniformity of the electrode foil is poor and the etched holes are serious. Figure 4 This is the cross-sectional morphology of the etched holes in the electrode foil obtained in Comparative Example 1, from which it can be seen that the consistency of the tunnel hole length is poor.

[0189] (2) Electrode foil capacity detection.

[0190] Specific capacity test method: The electrode foil is subjected to 520V chemical treatment in a 10% boric acid solution at 90°C, and then a ZX8516B electrostatic capacity tester of Changzhou Zhixin Precision Electronics Co., Ltd. is used, with a measurement accuracy of ±2%, a test frequency of 120±5Hz, a measurement voltage of less than 0.5Vrms, and a bath composition of 1000mL pure water, 80g ammonium pentaborate, and a test temperature of 30±2°C.

[0191] (3) Bending strength test.

[0192] Bending performance test method: The size of the electrode foil is 10mm*150mm (the punching burr should be less than 0.1mm). The MIT-DA bending tester of YAFENG is used. The test conditions are the curvature radius of the bend R1.0±0.1mm, the load 2.5±0.5N, the bending angle 90±2°, the bending reciprocating speed 6 times / S, and the distance between the upper and lower chucks 70±2mm.

[0193] The test results are shown in Table 1.

[0194] Table 1 Summary of electrode foil performance results in the embodiments of the present invention and the comparative examples

[0195]

[0196]

[0197] Combination Figure 1-4 As can be seen from Table 1, the porous titanium dioxide film is first formed on the surface of the aluminum foil by the preparation method of the present invention, and the specific capacitance of the electrode foil thus prepared is not less than 0.879 μf / cm 2 , the number of bends shall not be less than 72 times.

[0198] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A method for preparing an electrode foil, characterized in that: The method comprises forming a porous titanium dioxide film on the surface of the aluminum foil before pre-treating the aluminum foil.

2. The method for preparing the electrode foil according to claim 1, characterized in that: The method of forming the porous titanium dioxide film on the surface of the aluminum foil comprises: preparing a titanium dioxide sol by a sol-gel method, coating the titanium dioxide sol on the surface of the aluminum foil by a pulling and impregnation method, and forming the porous titanium dioxide film after drying; Preferably, the pore size of the porous titanium dioxide membrane is 100 nm to 200 nm.

3. The method for preparing the electrode foil according to claim 2, characterized in that: The titanium dioxide sol comprises a solvent and a titanium source; Preferably, the solvent comprises polyethylene glycol and polyethylene; Preferably, the titanium source includes butyl titanate and titanium tetrachloride; Preferably, based on the total mass of the titanium source and the solvent, the mass percentage of the polyethylene glycol is 0.05% to 2%; Preferably, in the solvent, the mass ratio of polyethylene glycol to polyethylene is 1-3:1.5-9; Preferably, in the titanium source, the mass ratio of butyl titanate to titanium tetrachloride is 1-3:4-8; Preferably, the temperature of the titanium dioxide sol in the pulling and impregnation method is 30°C to 60°C, and the pulling speed is 10mm / min to 100mm / min; Preferably, the drying temperature is 70° C. to 120° C., and the drying time is 20 min to 60 min.

4. The method for preparing an electrode foil according to claim 1, characterized in that: The treatment liquid used in the pretreatment is a solution containing hydrochloric acid and phosphoric acid; Preferably, in the treatment solution used in the pre-treatment, the mass percentage of hydrochloric acid is 5% to 10%, and the mass percentage of phosphoric acid is 3% to 20%; Preferably, the pretreatment temperature is 30°C to 80°C; Preferably, the pretreatment time is 1 min to 20 min.

5. The method for preparing the electrode foil according to claim 1, characterized in that: The preparation method further comprises performing primary pore forming and secondary pore expansion after the pre-treatment.

6. The method for preparing the electrode foil according to claim 5, characterized in that: The first-level hole is made of a corrosive solution containing aluminum ions; Preferably, the mass percentage of aluminum ions in the etching solution is 2% to 10%; Preferably, the corrosive solution is an acidic solution containing aluminum ions; Preferably, the etching solution contains hydrochloric acid and sulfuric acid; Preferably, the etching solution contains 3.0% to 10.0% by mass of hydrochloric acid and 20% to 40% by mass of sulfuric acid; Preferably, the temperature of the primary pore is 50°C to 90°C; Preferably, the time of the first-level pore generation is 10s to 60s.

7. The method for preparing the electrode foil according to claim 5, characterized in that: The secondary pore expansion uses an electrolyte containing aluminum ions; Preferably, the mass percentage of aluminum ions in the electrolyte is 0.5% to 4.5%; Preferably, the electrolyte is an acidic solution containing aluminum ions; Preferably, the electrolyte contains nitric acid and phosphoric acid; Preferably, the electrolyte contains 2.5% to 7.5% by mass of nitric acid and 0.02% to 0.25% by mass of phosphoric acid; Preferably, the temperature of the secondary hole expansion is 60°C to 95°C; Preferably, the current density of the secondary hole expansion is 0.1A / cm 2 ~3A / cm 2 ; Preferably, the effective power-on time for the secondary hole expansion is 6 minutes to 30 minutes.

8. The method for preparing an electrode foil according to claim 1, characterized in that: The preparation method also includes post-processing; Preferably, the post-treatment uses a solution containing nitric acid; Preferably, the mass percentage of nitric acid in the solution containing nitric acid is 3% to 10%; Preferably, the post-treatment temperature is 60°C to 80°C; Preferably, the post-treatment time is 1 min to 10 min; Preferably, the preparation method further comprises removing the porous titanium dioxide film before performing the post-treatment; Preferably, the porous titanium dioxide film is removed by a drying method, the drying temperature is more preferably 50° C. to 100° C., and the drying time is more preferably 20 min to 60 min.

9. An electrode foil, characterized in that: The electrode foil is prepared by the preparation method described in any one of claims 1 to 8.

10. An aluminum electrolytic capacitor, characterized in that: The aluminum electrolytic capacitor comprises an electrode foil prepared by the preparation method according to any one of claims 1 to 8 or the electrode foil according to claim 9.

Citation Information

Patent Citations

  • Antibacterial aluminum foil composite material and manufacturing method thereof

    CN108705820A

  • Preparation method of aluminum electrolytic capacitor anode foil composite film

    CN113161150A

  • Preparation method of high-dielectric-constant composite anode oxide film

    CN113718310A

  • Thin film anode material with nanopore channel confinement structure as well as preparation method and application of thin film anode material

    CN117945510A

  • Piezoelectric structure and its manufacture

    JP1999031857A